Henry Jefferson Leovy, The Laws and General Ordinances of the City of New Orleans 257,§ 636(5) (1870) - (:unkn) unknown (My University, 1870)
636(5): Prohibited unlicensed shooting galleries from operating within city limits.
Keywords: SHOOTING RANGES OR GALLERIES